Promoting low socio-economic participation in higher education: a comparison of area-based and individual measures - Dockery, Alfred Michael; Seymour, Richard; Koshy, Paul (Routledge, 2015)
As with other countries, Australia has been grappling with the identification, measurement and impact of disadvantage in higher education. In particular, the measurement of socio-economic status (SES) has been of central concern. The immediate solution in Australia has been the introduction of an ‘area’ measure in which students' SES is categorised on the basis of census data for their neighbourhoods rather than on individual or household data. This paper assesses the veracity of the area measure in capturing individual SES for school-aged entrants, using a longitudinal data set, the Household, Income and Labour Dynamics in Australia (HILDA) Survey, to construct individual measures of SES and a national ranking of sample individuals on the basis of probability of attending a higher education institution. The results demonstrate the tendency for area measures to misclassify individuals' higher education opportunity and the associated potential for perverse policy outcomes.